A Follow-Up Investigation of Mental Health Among Discharged COVID-19 Patients in Wuhan, China - Li, Li; Wu, Michael Shengtao; Tao, Junxiu; Wang, Weijun; He, Jing; Liu, Ru; Guo, Juan; Chen, Yun; Li, Kejian; Li, Shilong; Qi, Bo; Han, Buxin (Frontiers in Public Health, 2021)
Objective: To understand the mental health status and its risk factors among discharged COVID-19 patients during the first-month centralized quarantine and the subsequent home isolation. Methods: The scales of Insomnia severity Index (ISI), General Anxiety Disorder (GAD-7) and Patient Health Questionnaire (PHQ-9) were used to measure the symptoms of insomnia, anxiety, and depression in 782 COVID-19 patients during the first-month centralized quarantine (on March 16 to 26, 2020) and then in the home isolation (on April 3 to 10, 2020). Results: During the centralized quarantine, the prevalence rates of insomnia, anxiety and depressive symptoms were 44.37%, 31.59% and 27.62%, respectively, and those during the home isolation decreased significantly, which were 27.11%, 17.26% and 16.11%, respectively. In both waves, women showed a higher prevalence rate of mental symptoms as compared to men, and middle-aged and elderly (over 40 years old) showed a higher rate of mental symptoms as compared to the younger. In addition, the severity of COVID-19 revealed no significant relationship to mental symptoms, whereas the interaction analysis revealed that those with other underlying diseases showed more mental symptoms during the centralized quarantine and greater decrease during the follow-up home isolation. Conclusion: The discharged COVID-19 patients suffer from mental problems such as insomnia, depression and anxiety, especially for females, the middle-aged and elderly, and those with underlying diseases, but along with the rehabilitation and the environmental change from centralized quarantine to home isolation, all the mental symptoms were significantly alleviated. Based on a follow-up investigation, the current results provide critical evidence for mental health and early therapy upon the discharged COVID-19 patients.